Peningkatan Produktivitas Kinerja pada Universitas XYZ Menggunakan Metode Marvin E Mundel - Susiati, Devi; Pradana, Franky Rangga (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The development of the world of education requires university institutions to continue to increase innovation and productivity so that they can be highly competitive. Factors that are very influential in improving the quality of the University are lecturers and students. For this reason, XYZ University must be able to adapt to technological developments so that it can respond quickly to global market needs. With this phenomenon, XYZ University, especially the Faculty of Engineering, needs skilled workers in the engineering field so as to produce graduates who have relevant abilities and skills. The current vision of the Faculty of Engineering is "To become a superior and competitive engineering faculty in the Southeast Asia region by 2035". To realize this vision, Engineering is required to always improve the quality of the education process, research and community service accompanied by efforts to increase its relevance in the context of global competition. In the future, FT-XYZ is expected to be able to have quality that is on par with engineering faculties from leading universities in Southeast Asia in terms of the quality of the learning process and graduates, research and community service, so that it can raise the honor and dignity of the Indonesian nation. The steps taken are to increase the productivity of workforce performance. Therefore, the Marvin E Mundel method was used to analyze performance productivity, factors that experienced increases or decreases. The results of these calculations show that the alternative chosen with the highest productivity increase value is alternative 3, namely by increasing input slightly and increasing output more. The value obtained based on alternative 3 is 256.38%, with a drastic increase of 156.38% from the initial productivity.